Penyusunan Disaster Recovery Plan (DRP) berdasarkan Framework NIST SP 800-34 (Studi Kasus: Departemen Teknologi Informasi PT Pupuk Kalimantan Timur) - Adi Supriyanto; Ismiarta Aknuranda; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Information Technology (IT) in the industrial world currently plays a vital role in the sustainability of business processes, including PT Pupuk Kalimantan Timur. To maintain the continuity of its business process activities, PT Pupuk Kalimantan Timur realizes the need for continuous control efforts. This control effort is closely related to the increased risk of implementing IT at PT Pupuk Kalimantan Timur. Risks that have a negative impact have the potential to threaten the sustainability of the organization's business activities if they reach certain criteria that make it a disaster. This is what drives PT Pupuk Kalimantan Timur to prepare itself for the possibility of a disaster. This study aims to prepare a Disaster Recovery Plan (DRP) for PT Pupuk Kalimantan Timur. DRP is a type of contingency plan that includes organizational preparation and response when a disaster occurs. The drafting of the DRP is guided by the NIST SP 800-34 framework that begins with the identification and assessment of risks, Business Impact Analysis (BIA), identification of preventive controls and preparation of contingency strategies. After the steps are carried out, the research is continued with the development of a contingency plan that includes plans for the activation phase, recovery phase and reconstitution phase. The results of this study are DRP documents that are adapted to the conditions of the PT Pupuk Kalimantan Timur organization. This DRP document contains guidelines for service recovery along with preventive measures before a disaster occurs.